Conducting and stretchable emulsion styrene butadiene rubber composites using SiO2@Ag core-shell particles and polydopamine coated carbon nanotubes. (November 2022) - Li, Qiao; Lin, Guangyi; Zhang, Su; Wang, Haitong; Borah, Jyotishmoy; Jing, Yuan; Liu, Fumin
Abstract: In the present scenario of development in technology, the applications of stretchable conductive elastomers in modern electronic equipments have aroused great interest. Non-covalent bonding modification of carbon nanotubes (CNTs) using dopamine has improved the dispersion of CNT@PDA and interfacial interaction with the rubber matrix. The SiO2 @Ag core-shell particles were prepared by coated with silver nanoparticles (AgNPs) on the surface of SiO2 using dopamine oxidation self-polymerization and electroless plating process. ESBR composites were prepared by latex co-coagulation method, where CNT@PDA and SiO2 @Ag were used to develop an 1D-3D synergistic conductive network in ESBR composites. One-dimensional (1D) CNT@PDA were incorporated in three-dimensional (3D) spherical SiO2 @Ag core-shell particles, which effectively prevented the agglomeration of SiO2 @Ag and CNT@PDA. Again, 1D CNT@PDA could also be used as bridges to interact with 3D SiO2 @Ag to develop the charge transfer more effectively in ESBR composites. The optimum electrical conductivity of the ESBR/CNT@PDA/SiO2 @Ag composites was 0.2 S/cm, which was found to be higher than that of single filler. Moreover, the high electrical conductivity can be controlled at low tensile strain. The mechanical property of ESBR/CNT@PDA/SiO2 @Ag composite was also improved by 105.4% as compared by ESBR/CNTs. This work provides a new idea for the fabrication of stretchable conductive elastomer composites with high performance. Highlights: SiO2 @Ag core-shell particles were prepared by dopamine oxidation self-polymerization and electroless plating process. PDA was used to modify CNTs by non-covalent binding interaction. CNT@PDA and SiO2 @Ag were used to develop an 1D-3D synergistic conductive network. The high electrical conductivity can be maintained at low tensile strain.